Bentuk Aktualisasi Diri dalam Novel Luka Cita Karya Valerie Patkar Berdasarkan Kajian Psikologi Carl Rogers - Nada Vanca Anggrestia; Taswirul Afkar; Wawan Hermawan (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the forms of self-actualization in Valerie Patkar's Luka Cita novel based on Carl Rogers' humanistic psychology study. The main problem in this study focuses on how the forms of self-actualization that include openness to experience, existential life, and belief in organisms, and how the psychological implications of the process are depicted through the main character. The purpose of this study is to describe the forms of self-actualization and their implications through Carl Rogers' perspective. This study uses a qualitative descriptive method with a reading-note technique, and is analyzed using a content analysis technique. The results of the study indicate that the main character displays the process of self-actualization through five types of openness to experience, namely openness to action, to ideas, values, aesthetics, and feelings. The aspect of existential life is depicted through the ability to live in the present moment, flexibility in responding to experience, and the ability to find meaning from experience. Meanwhile, belief in organisms is seen through the use of affirmative, anticipatory, and conclusive intuition in decision making. The implications of the form of self-actualization include existential freedom (freedom to choose, act, and determine), creativity (mimetic, biosocial, analogous, narratological, and intuitive), fundamental honesty in human nature (constructive and trustworthy), and increasing intensity of life through openness to emotions as a whole, emotional complexity, and courage to face emotional reality. The conclusion of this study is that the main character successfully actualizes himself and produces psychological implications from the form of self-actualization.